Vaccination coverage and abandonment among children under two years old in Brazil: a time-series study - Rossana Marchese Bittencourt Enore; Bruna Hinnah Borges Martins de Freitas; Ronaldo Antonio da Silva; Maria Aparecida Munhoz Gaíva (Sociedade de Pediatria de São Paulo, 2024)
ABSTRACT Objective: To analyze the vaccination coverage and abandonment rates among children under two years old in Brazil, from 2015 to 2021. Methods: A time-series ecological study. The dependent variables of the research were "vaccination coverage" and "abandonment rate", both assessed by Brazilian region. The data were extracted in July 2022 from the Information System of the National Immunization Program. The Prais-Winsten technique was used for the trend analysis, with the aid of the STATA 16.0 software. Results: The mean vaccination coverage in Brazil was 76.96%, with a decreasing trend during the period (Annual Percent Change=-5.12; confidence interval - CI95% -7.81; -2.34); in 2015, the rate was 88.85% and it dropped to 62.35% in 2021. In turn, the overall abandonment rate was 24.00% in 2015 and 9.01% in 2021, with a mean of 10.48% and a stationary trend (Annual Percentage Change=-9.54; CI95% -22.92; 6.12). In 2021, all the vaccines presented coverage values below 74.00% in the country. Conclusions: The vaccination coverage rate trend among children under two years old was stationary or decreasing for all the immunobiologicals in all Brazilian regions, with the exception of yellow fever in the South and Southeast regions. There was an increase in the abandonment rate trend for the Meningococcal C vaccine in the country and, specifically in relation to the regions, for BCG in the North, Northeast, and Midwest and for Meningococcal C in the North and Northeast.